A sustainable forest management criteria and indicators assessment using fuzzy analytic hierarchy process - Bayram, Bahadır Çağrı (Springer Science and Business Media LLC, 2021)
Today, resource depletion has become a worldwide issue due to the increasing human population and related consumption. Therefore, the sustainability of renewable natural resources has recently gained great importance. To achieve a more sustainable world, sustainable development is needed. In sustainable development, the sustainable forestry holds an important part because of forests' great importance among the natural resources. Thus, the sustainable forest management (SFM) practices have been vital at this point. The present paper aims to contribute SFM applications and literature with the evaluation and interpretation of the National SFM of Turkey by calculating the importance levels (weights) of latest criteria and indicators (C&I). For this purpose, Fuzzy Analytic Hierarchy Process (AHP), a hybrid approach of fuzzy logic and multi-criteria decision-making, was adopted. This adoption is due to the complex and hierarchical framework of sustainability and the suitability of the method to the subject. The present research is a case study from Kastamonu Regional Directorate of Forestry. Kastamonu holds an important part in Turkish forestry, and it has the potential to represent general condition. This study has shown that the importance attached to environment-related C&I is considerably higher than that of other SFM C&I. Furthermore, Turkey focuses more on the sustainability of wood and wood products rather than other sustainability indicators. The research has also identified that there is a classification problem for SFM indicators. The current C&I should be reviewed and localized.
Keywords: Conservation of Natural Resources; Turkey; Forestry; Forests; Analytic Hierarchy Process; Fuzzy Logic; Humans; Environmental Monitoring; 15. Life on land; 12. Responsible consumption; 13. Climate action; 11. Sustainability